Drama and the struggle for social change Zimbabwe: the case of Tsitsi Dangarembga’s She Nolonger Weeps, George Mujajati’s The Wretched Ones and Raisedon Baya and Leonard Matsa’s Super Patriots and Morons, - Mucheke, Noreen (Midlands State University, 2014)
Despite this rich use to which drama has been put in Zimbabwe, schools, colleges and Universities have largely sidelined the study of drama (plays) on the official syllabi in preference to other genres such as the short story, poems and the novel, as if drama has not richly debated societal challenges by contesting the various levels of inequalities, power relations and social trends that need correction in the Zimbabwean society. This is glaringly clear in the Department of English and Communication at Midlands State University which prioritises the novel, short stories and to some extent poems to drama. Ask any student in the Department which plays he or she has studied, most probably they will not be able to name more than two that they have studied apart from Shakespeare’s plays.